C‐MYC–positive relapsed and refractory, diffuse large B‐cell lymphoma: Impact of additional "hits" and outcomes with subsequent therapy. Issue 22 (27th July 2017) - Epperla, Narendranath; Maddocks, Kami J.; Salhab, Mohammed; Chavez, Julio C.; Reddy, Nishitha; Karmali, Reem; Umyarova, Elvira; Bachanova, Veronika; Costa, Cristiana; Glenn, Martha; Calzada, Oscar; Xavier, Ana C.; et al.
Abstract : BACKGROUND: The impact of MYC proto‐oncogene, basic helix‐loop‐helix ( MYC ) translocations (with or without additional rearrangements involving the B‐cell lymphoma 2 [ BCL2 ] or BCL6 genes) on the response to salvage therapy and survival in patients with diffuse large B‐cell lymphoma (DLBCL) who experience primary treatment failure is not well defined. METHODS: This was a multicenter, retrospective study of the impact of MYC, BCL2, and BCL6 rearrangements in patients with DLBCL who failed to achieve complete remission or relapsed within 6 months after they completed upfront chemoimmunotherapy. RESULTS: The authors examined response to salvage therapy, receipt of hematopoietic cell transplantation (HCT), and survival outcomes in MYC ‐negative (n = 120), MYC ‐positive single hit (SH) (n = 20), and MYC ‐positive double hit/triple hit (DH/TH) (n = 35) cohorts. The overall response rate in these cohorts to first salvage therapy (51%, 50%, and 54%, respectively) and receipt of HCT (52%, 40%, and 43%, respectively) were comparable between the 3 cohorts. The 2‐year overall survival rate was 29.9% in the MYC ‐negative cohort, 0% in the MYC ‐positive SH cohort, and 9.9% in the MYC ‐positive DH/TH cohort ( P < .001), and no difference was observed between the SH and DH/TH cohorts ( P = .8). The higher risk of death for patients with MYC ‐positive SH DLBCL (hazard ratio, 1.70; 95% confidence interval, 0.98‐2.96; P = .06) and those with MYC ‐positive DH/TH DLBCL (hazard ratio, 2.22; 95% confidence interval, 1.41‐3.50; P = .001) persisted after adjusting for covariates. For patients who underwent autologous HCT, the 2‐year overall survival rate was 55.4% in the MYC ‐negative cohort, 0% in the MYC ‐positive SH cohort, and 19.4% in the MYC ‐positive DH/TH cohort ( P < .001). All 4 MYC ‐positive patients who underwent allogeneic HCT relapsed in <4 months. CONCLUSIONS: Patients with MYC ‐positive DLBCL who experience primary treatment failure have response rates to similar to those achieved by salvage therapy compared with their MYC ‐negative counterparts, but their survival is dismal irrespective of additional "hits" and HCT, representing an unmet medical need. Cancer 2017;123:4411‐8 . © 2017 American Cancer Society . Abstract : The impact of MYC translocations (with or without additional BCL 2 or BCL 6 gene rearrangements) on response to salvage therapy and survival in patients with diffuse large B‐cell lymphoma who experience primary treatment failure is not well defined. In this retrospective study, patients with MYC ‐positive DLBCL who fail on primary treatment have response rates similar to those observed after salvage therapy compared with their MYC ‐negative counterparts, but their survival is dismal irrespective of additional "hits" and hematopoietic cell transplantation, representing an unmet medical need.